Identification of important actions for Musi Rawas Utara Regency to become an agile government - Sari, Marlinda; Alfitri, Alfitri; Nadjib, Abdul; Fefta, Andy (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
This paper aims to provide a formulation related to implementing the AgileGovernance strategies in the management of the Muratara Regency Government during the COVID-19 pandemic towards the Era of Society 5.0. This study uses a qualitative content analysis method. This method emphasizes the analysis, synthesis, and providing recommendations based on a scientific understanding of academic writing. The results of the paper concluded that the implementation of agile governance strategies during the COVID-19 pandemic towards the Era of Society 5.0 in the Muratara Regency Government is: (a) the need to share goals and visions with all members of the organization, seek opportunities and measure the existing options, flexible use of resources, and instructions on strategies that can be implemented. (b). The need for a leader of change who is a catalyst and strengthens the team’s network (c). The needs for organizations that carry out constant learning. (d). The need for implementing an open communication style. (e). The need for a clean organization that follows good governance. (g). The need to develop employee competency (individual).